THE MUSEUM AND THE SCHOOL - Allard, Michel; Boucher, Suzanne; Forest, Lina (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1994)
This paper is a summary of research done by the Groupe de recherche sur l’éducation et les musées (GREM) to develop a teaching model for the use of museums for educational purposes. The background of the study is presented, followed by a description of the basic findings. In the first section, essential characteristics of educational programs relating to the learning process, the use of a theme, and objectives are analyzed. This is followed by a description of some program activities held before, during, and after a museum visit. In conclusion, some of the research methods are discussed. RÉSUMÉ Cet article résume les travaux conduits parle Groupe de recbercbe sur l’éducation et les musées afin de développer un modèle didactique d’utilisation des musées à des fins éducatives. Les origines de la recherche sont d’abord décrites. Puis, les résultats les plus fondamentaux sont présentés. Premièrement, les caractéristiques essentielles des programmes éducatifs se rapportant à la démarche d’apprentissage, à l’utilisation d’un thème et aux objectifs sont analysées. Par la suite, des activités tenues avant,pendant et après la visite au musée illustrent le modèle. En conclusion, quelques pistes de recherche sont indiquées.